Formulation and Assessment of Nutritious Complementary Food Blended with Germinated (Maize, Millet and Soybean), Carrot, and Coconut Flour - Season Khanal; Bishal Thagunna; Sonika Ghimire; Ishori Bhandari; Binod Sunar (Biology, Medicine, & Natural Product Chemistry, 2026)
In developing nations, malnutrition related to protein and energy in young children is possibly the most widespread health issue. Complementary foods are essential for the growth and development of children as they address both the nutritional and developmental requirements of infants when breastfeeding alone is insufficient. The purpose of this study was to evaluate effects of blending ratio and processing technique on physicochemical composition, and sensory acceptability of quality germinated maize, millet, and soybean, along with carrot and coconut flour based complementary food. The different staples were processed into flours and were combined in ratios of (70:10:10: 5:5), (60:15:15:5:5), (50:20:20:5:5), and (40:25:25:5:5) of maize flour, millet flour, soybean flour, carrot and coconut flour and the samples were denoted as A, B, C, and D. The result revealed that composite the moisture levels varied from 6.55% to 7.15%, with sample C containing 50% maize flour exhibiting the highest moisture content, while sample D with 40% maize flour showed the lowest moisture content. The protein content values of all samples exceeded the 15%. The fat content of the complementary food samples varied between 6.44% and 8.58%, showing highest in sample highest in sample A and lowest in sample E. The range of crude fiber content varied from 1.89% to 4.73%, with sample D showing the highest level and sample E the lowest. The ash content of the formulated complementary food samples increased with the rising addition of maize, soybean, and millet flour. From the sensory analysis sample C recorded the highest score.